Immunological changes after COVID-19 vaccination in an HIV-positive patient - Gong, Changlin; Song, Xiaojing; Li, Xiaoxia; Lu, Lianfeng; Li, Taisheng (International journal of infectious diseases, 2022)
•Vaccination is an essential and promising way to cope with the COVID-19 pandemic.•We report the case of an HIV-positive patient showing deterioration after vaccination.•Caution should be taken when vaccinating HIV-positive patients who are not on medication. Vaccination is an essential measure to stop the coronavirus disease 2019 (COVID-19) pandemic. We report a case of viral activation and CD4+ T cell loss in a treatment-naïve HIV-positive patient after receiving inactivated COVID-19 vaccine (Sinopharm). The vaccine should probably be given only to people living with HIV receiving antiretroviral therapy.